Penafsiran Kontemporer al-Qur’ān terhadap Isu-Isu Hak Asasi Manusia (HAM) Perempuan - Yeni Huriani (ILMU USHULUDDIN, 2013)
The emergence of human rights issues related to women has developed considerable debates in various academic approaches. For some Muslim scholars, human rights of women are linked to the perspective of interpretation of the Qur’ānic verses, which are still considered misogyny (view of ignoring women.) The focus of this study is to examine how the contemporary interpretation of the Qur’ān on women’s rights issues. The method used is a critical-analytical method. The results of this study show that there is still interpretation of the Qur’ān about women’s rights issues that are misogyny. Women are positioned based on their gender, not on their capacities and competencies. Whereas the Qur’ān obviously contains clues about the necessity to put every person, including women, in the nature of humanity as khalīfa fī al-ard, who have opportunity and equal access with men on the roles are undertaken.